A Model for Transport Phenomena in a Cross-Flow Ultrafiltration Module with Microchannels - Shiro Yoshikawa (Membranes, 2010)
Cross-flow ultrafiltration of macromolecular solutions in a module with microchannels is expected to have the advantages of fast diffusion from the membrane surface and a high ratio of membrane surface area to feed liquid volume. Cross-flow ultrafiltration modules with microchannels are expected to be used for separation and refining and as membrane reactors in microchemical processes. Though these modules can be applied as a separator connected with a micro-channel reactor or a membrane reactor, there have been few papers on their performance. The purpose of this study was to clarify the relationship between operational conditions and performance of cross-flow ultrafiltration devices with microchannels. In this study, Poly Vinyl Pyrrolidone (PVP) aqueous solution was used as a model solute of macromolecules such as enzymes. Cross-flow ultrafiltration experiments were carried out under constant pressure conditions, varying other operational conditions. The permeate flux decreased in the beginning of each experiment. After enough time passed, the permeate flux reached a constant value. The performance of the module was discussed based on the constant values of the flux. It was observed that the permeate flux increased with increasing transmembrane pressure (TMP) and feed flow rate, and decreased with an increase of feed liquid concentration. A model of the transport phenomena in the feed liquid side channel and the permeation through the membrane was developed based on the concentration and velocity distributions in the feed side channel. The experimental results were compared with those based on the model and the performance of the ultrafiltration module is discussed.